2016
DOI: 10.1016/j.jvs.2016.04.059
|View full text |Cite
|
Sign up to set email alerts
|

Development of a risk prediction model for transfusion in carotid endarterectomy and demonstration of cost-saving potential by avoidance of “type and screen”

Abstract: Objectives Preoperative testing for carotid endarterectomy (CEA) often includes blood typing and antibody screen (T&S). In our institutional experience, however, transfusion for CEA is rare. We assessed transfusion rate and risk factors in a national clinical database to identify a cohort of patients in whom T&S can safely be avoided with the potential for substantial cost savings. Methods Using the NSQIP database, transfusion events and timing were established for all elective CEAs in 2012–13. Comorbidities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
2
10
1
Order By: Relevance
“…population, amounting to potential savings of more than $5.2M. 23 This 5% transfusion threshold is widely supported in the literature. 1,25,26,37 We too identified a similar threshold using one-way sensitivity analysis, which demonstrated that the risk of transfusion should exceed 4.12% to justify preoperative T/S.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…population, amounting to potential savings of more than $5.2M. 23 This 5% transfusion threshold is widely supported in the literature. 1,25,26,37 We too identified a similar threshold using one-way sensitivity analysis, which demonstrated that the risk of transfusion should exceed 4.12% to justify preoperative T/S.…”
Section: Discussionmentioning
confidence: 92%
“…[33][34][35][36] The additional risk factors identified in this analysis, such as liver disease and widespread cancer, can be used to develop a transfusion prediction model, similar to the case for carotid endarterectomy. 23 Using a 5% predicted transfusion risk threshold, the referenced authors concluded that a preoperative T/S can safely be avoided in 93% of their studied Fig. 2 One-way sensitivity analysis of variability in rate of transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…We chose a threshold of 5% based on prior work related to avoiding type and screen in patients undergoing carotid endarterectomy. 30 This threshold is likely overly conservative, and can be modified depending on the characteristics of the individual centers. For example, centers with robust, well-developed massive transfusion protocols and electronic type and cross can apply higher thresholds, whereas centers without those capabilities can use a lower score.…”
Section: Discussionmentioning
confidence: 99%
“…While numerous studies associate bleeding and transfusion with several perioperative and surgical factors, source data are often based on a single‐center experience, are missing key covariate data, and yield inconsistent results 5,6,11–16 . Although transfusion prediction models have been developed for several surgical procedures, such as head and neck cancer surgery, coronary artery bypass graft surgery, total joint arthroplasty, and carotid endarterectomy, these models are often limited primarily to adult patients 17–20 . The categorization of transfusion risk based on characteristics known preoperatively is in its early stages in pediatric surgical patients, and the current literature encourages more investigation to enable reliable risk stratification and to enhance preoperative planning in this population 6,21 …”
Section: Introductionmentioning
confidence: 99%